The comparison of the effectiveness of group training on the concepts of positivist psychology and metacognition on the level of anxiety and resilience of female adolescents during the Coronavirus pandemic quarantine - Narimani, Fariba; Azmoudeh, Masoumeh; Livarjani, Sholeh; Mesrabadi, Javad (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to compare the effectiveness of group training plan of positive psychology intervention and metacognition training on anxiety and resilience of female adolescents in Coronavirus pandemic quarantine. Methods: This study was quasi-experimental with a pre-test-post-test design, a control group and a follow-up period. A total of 90 adolescent girls were selected by multi-stage cluster random sampling method, and were randomly assigned into three equal groups (two experimental groups and one control group, and each group included 30 people. The experimental group of metacognition received the combined training package of Wales and Robinia training package in eight sessions of 90 minutes per week, and the experimental group of positive psychology received the combined package of Cheraghian (2014) and the training package (AFMAS) in 9 sessions of 90 minutes per week. All three groups were evaluated in three stages pre-test, post-test, and a three-month follow-up using Anxiety Scale (1990) and Connor-Davidson (2003) Resilience Scale Measure. The data were analyzed using repeated-measures analysis of variance. Results: The findings indicated that group training of positive psychology (F = 10.91, P = 0.002) and metacognition (F = 11.92, P = 0.001) was effective on anxiety, and group training of positive psychology (F=16.50, P = 0.001) and metacognition (F = 812.77, P = 0.001) were effective on the level of resilience. And there was no significant difference between the effects of the two types of training. Conclusion: It was accordingly concluded that both positive and metacognitive training methods were effective in reducing anxiety and increasing the resilience of female adolescents.